Dinâmica de populações de cianobactérias em reservatório eutrofizado no semi-árido nordestino brasileiro - Costa, Ivaneide Alves Soares da (Universidade Federal de São Carlos, 2003)
The Armando Ribeiro Gonçalves reservoir, located in the semi-arid of the Rio Grande do Norte (06o08 S ; 37o 07 W), in Northeast Brazil, represents 68% of the total surface water accumulated in the state. The reservoir, with maximum volumetric capacity of 2.4 x 109, provides 400 thousands habitants and also is destined to irrigation, leisure and fishing. It has permanent and continuos blooms of potentially toxic cyanobacteria. The aim of this paper were to identify the planktonic cyanobacteria, to recognize the temporal patterns of population distribution, understanding the environmental factors regulating dominance, and to distinguish and quantify the cyanotoxins present in the reservoir s crude water seston and in the treated water at the treatment station outlet (ETA). According to the region s climatic characteristics, the investigations were carried out from 2000 to 2002. The samples for cyanobacteria identification (n=36) were collected with plankton net and preserved with formol 4%. In order to detect phitoplankton temporal variations, 22 samples were collected (300mL) and preserved with lugol solution. This was done in short period of time (4 days) in the 2000 annual cycle, in the rainy season (April and May/n=8), intermediate (May and July) and dry (november and December/ n=10) seasons, in 7 depths (surface, 10% and 1% of light penetration, in 5m, 10 and bottom =21), and in 300 meters from the reservoir major slope. At the same time, water samples for nutrient ad toxins analysis were collected. The samples for cianotoxins analysis were collected in the reservoir (n=9), in the Pataxó Channel (n=4 open channel for water transport to ETA) and in the local ETA distribution exit (n=4). Climatic factors were analyzed (wind, rain, temperature), as well as hydrological (residence period, volume), physical (Zeu, water temperature) and chemical (electric conductivity, suspension matter, both organic and inorganic, alkalinity, free and total CO2, HCO3 -, O2, NO3 -,NH4 +, NTD, NT, PSR,PTD, PT e N:P). The phytoplankton community attributes (diversity, equitability, abundance and biomass expressed in biovolume mm3.L-1) and the cyanotoxin determination (microcistins, saxitoxins e cylindrospermopsin) by HPLC technique and ELISA were also analysed. We have identified 28 phitoplankton taxa, 20 cyanobacteria taxa (71%), 5 cloroficeae (18%) and 4 diatomacea (14%). Among the cyanobacteria, 50% are potentially toxic, distributed in 12 genera represented by 12 species. Four of these genera are not typical of their representative species (cf.) and four were identified in the genera level. Nostocales e Chroococcales were the orders better represented, with 10 and 8 taxa respectively, followed by Oscillatoriales with 3 taxa. The taxa are distributed in the following families: Nostocaceae (5genera/10species), Anabaena sp, Anabaena sp1, A.circinalis, A. viguieri, Aphanizomenon gracile, Aphanizomenon cf. manguinii, Aphanizomenon cf. issatschenkoi, Cylindrospermopsis raciborskii, Cylindrospermum sp e Raphidiopsis mediterranea; Merismopediaceae (3genera-3species), Coelomoron tropicalis, Snowella cf. lacustris, Sphaerocavun brasiliense; Microcistaceae (1genus-4species), Microcystis sp, M. protocystis, M. panniformis e M. novacekii; Pseudanabaenaceae (1genus/1specie), Geitlerinema unigranulatum; Oscillatoriaceae (1genus/1specie), Lyngbya sp; Phormidiaceae (1genus/1specie), Planktothrix agardhii. The species of Cyilindrospermopsis raciborskii, Microcyistis panniformis, M. protocystis, Aphanizomenon gracile and Aphanizomenon cf. manguinii had larger relative abundance (90-97%) and formed mixed, toxic, intense and alternated blooms during the 2000 annual cycle. The system presented polimitic circulation, with stratification during the rainy season and homoiothermal conditions in the dry season. The short time period btween the investigations made possible to verify the existence and intensity of disturbance in the system, allowing better evaluation and understanding of the forces controlling structure and succession patterns in the phitopkankton community. In the dry season the wind enabled the photic layer circulation in the system (Zeu=3m), influencing the nutrient availability and phitoplankton distribution pattern, providing the community with more stability. Climatic conditions and physical processes inherent to the reservoir were determinant to the thermal circulation in the system and mixing of deep layers. The environmental variables of larger influence in the cyanobacteria distribution were PSR, PT, NTD, CO2, Zeu, rains, and wind. The variation of these factors promoted the establishment of ecologically distinct periods, described using the functional groups approach by Reynolds et al. (2000). Therefore, we have identified the Cylindrospermopsis (Sn) dominance during rains, both thermallly and quimic stratificated, slow winds, low Zeu, low CO3 - and CO2 and high NH4 + and N:P values. Microcystis spp (M) dominated from the beginning of drought and system destratification, with higher Zeu, low NO3 - and PSR and high NH4 + and N:P levels. During drought, period of mixing column water, low Zeu, high NO3 -, PSR and low NH4 + and N:P levels, associations of H (Aphanizomenon spp, Anabaena spp), S1 (Planktothrix agardhii e Limnothrix), Chlorophyceae (F) and Bacillariophyeae (P), all associations adapted to poor light environments, coexisted maintaining larger uniformity in the biomass distribution. The presence of C. raciborskii in different environmental conditions confirms this species great niche amplitude and suggests less efficiency of their adaptive physiological specificity when comparing to Microcystis and Aphanizomenon, since it coexisted maintaining significant biomass during all annual cycle. The microcistinas (8.8 µg l-1/crude water and 0,26 µg/L-1/treated water) and saxitoxinas presence (3,14 µg l-1/gross water) points a permanent risk for domestic supply waters. The ingestion of small doses of microcistins, in the long term, by local population trough its accumulation in fish musculature has also to be considered, due to its potential capacity to promote carcinogens hepatic tumors. The prevalence of saxitoxin in the crude water (60%) alerts to the probability of larger distribution of this toxin in fresh water, more than what its knowm of today, specially in the semi-arid Brazil. The presence of cyanobacteria in treated water (8,2 x105 cel.mL-1) revels inefficiency in the cells removal in the ETAs and indicates the urgent need for regular monitoring, bloom control measures implementation, and inspection recommended by Brazil s Health Ministry, aiming the water quality and public health improvement.
Keywords: Limnologia; Eutrofização; Reservatórios; Semi-árido; Cianobactérias; Cianotoxinas; Reservoir; Eutrophication; Semi-arid; Cyanobacteria; Cyanotoxins; CIENCIAS BIOLOGICAS::ECOLOGIA